Exploring the potent antimalarial properties of Drimys beccariana Gibbs through molecular docking analysis utilizing advanced structure-based drug design techniques - Faizal Hermanto; Hestiary Ratih; Fikri Alatas; Titta Hartyana Sutarna (Journal of Advanced Pharmaceutical Technology & Research)
Original Article Exploring the potent antimalarial properties of Drimys beccariana Gibbs through molecular docking analysis utilizing advanced structure-based drug design techniques Hermanto, Faizal; Ratih, Hestiary1; Alatas, Fikri1; Sutarna, Titta Hartyana1 Author Information Journal of Advanced Pharmaceutical Technology & Research 15(4):p 326-331, Oct–Dec 2024. | DOI: 10.4103/japtr.japtr_126_24 Open